Learning leadership personified. An interview with Professor Stephen Preskill (Journal of Applied Learning and Teaching, 2023)
In this extensive interview with Stephen Preskill, we cover much ground. We kick off the discussion with Preskill’s latest book Education in black and white, about Myles Horton, a life-changing teacher and activist whose work at Highlander Folk School influenced the civil rights movement. Preskill discerns three major themes: anti-racism, dialogue and Horton’s exemplary life. We then move on to who could be considered heirs of Horton and other Highlander leaders, and Preskill cautions against the pitfalls of charismatic leadership. He shares his positive experiences as a lifelong learner in a Master of Fine Arts program and provides advice on how to deal with academic writing difficulties. Preskill is also the co-author of four books on teacher narratives, democratic discussion, and social justice leadership, which we discuss systematically. He recalls his best and worst discussions and talks about his favorite discussion protocols. Biographically, Preskill recalls his happy childhood and youth in a well-to-do family and being inspired to become a teacher by his positive experience of his university studies. In terms of academic career advice, he advises following our passions before highlighting his approachability and openness as a way of learning leadership.Stephen Preskill is professor emeritus at Wagner College in Staten Island, New York and a writing consultant at Columbia University. During his thirty years as a university professor (that included appointments at Carleton College and the University of St. Thomas in Minnesota, and being the Regents Professor of Education in the Department of Educational Leadership and Organizational Learning in the College of Education at the University of New Mexico), he specialized in American educational history and leadership studies. Before his distinguished academic career, he was an elementary and middle school teacher for nine years.